2019
DOI: 10.1021/acs.jpca.9b10325
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Excited-State Intramolecular Proton Transfer Processes of Benzothiazole Derivatives in Amino-polydimethylsiloxanes before and after Cross-Linking by CO2

Abstract: The changes in the ability of three fluorescent derivatives of 2-(2′-hydroxyphenyl)benzothiazole to undergo excited-state intramolecular proton transfer (ESIPT) processes have been correlated with the rheological properties of four amino-polydimethylsiloxanes with different molar masses and containing different amounts of monomer units with amino pendant groups, in the presence and absence of a crosslinking molecule, CO 2 . The changes lead to a variety of species (keto, enol, and enolate forms) in both the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Regarding ground-state properties, it was observed that compound P43 (1 μM) in aqueous acetonitrile (50%, v/v) presented an absorption maximum at 365 nm with a high-energy shoulder at 310 nm. Upon changing the pH from 7 to 1, the absorption peak was blue-shifted by 15 nm with a minor decrease in molar absorption; however, under alkaline conditions (pH 12), the absorption band centered at 365 nm was diminished with a new red-shifted absorption maximum appearing at 409 nm, as expected with the deprotonation of the ESIPT compounds . In the excited state, the authors reported that the imidazole nitrogen was protonated in an acidic medium (pH 1), interrupting ESIPT, which led to a hypsochromic effect with an emission at 445 nm.…”
Section: Fluorescent Imidazole Sensor Based On Esipt Processmentioning
confidence: 94%
“…Regarding ground-state properties, it was observed that compound P43 (1 μM) in aqueous acetonitrile (50%, v/v) presented an absorption maximum at 365 nm with a high-energy shoulder at 310 nm. Upon changing the pH from 7 to 1, the absorption peak was blue-shifted by 15 nm with a minor decrease in molar absorption; however, under alkaline conditions (pH 12), the absorption band centered at 365 nm was diminished with a new red-shifted absorption maximum appearing at 409 nm, as expected with the deprotonation of the ESIPT compounds . In the excited state, the authors reported that the imidazole nitrogen was protonated in an acidic medium (pH 1), interrupting ESIPT, which led to a hypsochromic effect with an emission at 445 nm.…”
Section: Fluorescent Imidazole Sensor Based On Esipt Processmentioning
confidence: 94%
“…For 16-17, both the emission maxima (542 nm) and Stokes shifts (~8800 cm −1 ) were observed at higher wavelengths. Thus, the emission produced by compound 15 is probably related to its ionized species [42]. Compounds 16-17 exhibit proton transfer in the excited state, and the emission is a result of this process.…”
Section: Synthesis and Photophysical Characterizationmentioning
confidence: 99%
“…This feature could be a result of scattering and may be an indication of aggregation of these compounds in PBS (pH 7.2), due to the presence of the long alkyl chains in these compounds, which are extremely hydrophobic. Significantly, Molecules 2021, 26, 6728 3 of 15 the similarity in shape and maxima wavelength compared to those of organic solvents, as well as the absence of additional red-shifted bands in PBS, indicates the absence of ionized species in the ground state for derivatives in this media [42,43].…”
Section: Synthesis and Photophysical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…2-(2′-hydroxyphenyl)benzazole derivatives are a widespread class of emitters that figures great relevance due to their photoacidity coupled to the phototautomerization processes of Excited State Intramolecular Proton Transfer (ESIPT) [5,[10][11][12][13][14]. Both photoreactions, i.e., proton transfer on the excited state inter or intramolecularly (ESPT and ESIPT), have being applied as fluorescent sensors [2,[15][16][17][18][19][20].…”
Section: * *mentioning
confidence: 99%